Focal lesion size poorly correlates with motor function after experimental traumatic brain injury in mice - Walter, Johannes; Mende, Jannis; Hutagalung, Samuel; Grutza, Martin; Younsi, Alexander; Zheng, Guoli; Unterberg, Andreas; Zweckberger, Klaus (PLOS ONE, 2022)
Background It remains unclear whether neurobehavioral testing adds significant information to histologic assessment of experimental traumatic brain injury (TBI) and if automated gait assessment using the CatWalk XT®, while shown to be effective in in the acute phase, is also effective in the chronic phase after experimental TBI. Therefore, we evaluated the correlation of CatWalk XT® parameters with histologic lesion volume and analyzed their temporal and spatial patterns over four weeks after trauma induction. Methods C57Bl/6 mice were subjected to controlled cortical impact (CCI). CatWalk XT® analysis was performed one day prior to surgery and together with the histological evaluation of lesion volume on postoperative days one, three, seven, 14 and 28. Temporal and spatial profiles of gait impairment were analyzed and a total of 100 CatWalk XT® parameters were correlated to lesion size. Results While in the first week after CCI, there was significant impairment of nearly all CatWalk XT® parameters, impairment of paw prints, intensities and dynamic movement parameters resolved thereafter; however, impairment of dynamic single paw parameters persisted up to four weeks. Correlation of the CatWalk XT® parameters with lesion volume was poor at all timepoints. Conclusion As CatWalk XT® parameters do not correlate with focal lesion size after CCI, gait assessment using the CatWalk XT® might add valuable information to solitary histologic evaluation of the injury site. While all CatWalk XT® parameters can be used for gait assessments in the first week after CCI, dynamic single paw parameters might be more relevant in the chronic phase after experimental TBI.
Gesehen am 17.05.2022